A study to analyze the different patterns of quid usage among subjects with chewer's mucosa - Saba Khan; Laxmikanth Chatra; K Prashanth Shensi; K M Veena; Prasanna Kumar Rao (Wolters Kluwer Medknow Publications, 2012)
Aim: Betel chewer's mucosa, although not considered as a potentially malignant lesion, has been suggested to be a precursor of oral submucous fibrosis (OSMF). Thus a study was undertaken to asses various quid chewing patterns in patients with chewer's mucosa and to evaluate possible association between chewer's mucosa and a particular quid usage patter. Materials and methods: The study was done on 150 subjects clinically diagnosed of having chewers mucosa lesion. After complete oral examination, a detailed habit history was taken through preformed questionnaire. The data obtained was analyzed using Chi-square test. Results: Among the 150 subjects males to female ratio was 8:2- Majority of the subjects were within the age group of 20 to 30 years and chewed a combination of betel leaf, arecanut, tobacco, lime- Majority of the subjects of chewer's mucosa used the quid for a duration of 1 to 5 years, a frequency of three to five quid per day. Conclusion: In the present study, chewers mucosa was seen in majority of the subjects who used the quid for a duration of 1 to 5 years, a frequency of three to five quid per day and chewed the quid containing betel leaf, arecanut, tobacco, lime as its constituents.